2021
DOI: 10.1155/2021/8357585
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of CD163 as a Prognostic Biomarker and Associated with Immune Infiltration in Glioblastoma Multiforme

Abstract: Background. Glioblastoma multiforme (GBM) is the most common and aggressive primary malignancy in adults with high aggression. The prognosis of GBM patients is poor. There is a critical need for novel biomarkers for the prognosis and therapy of GBM. Methods. Differentially expressed genes (DEGs) in GBM were screened using TCGA cohort. Univariate and multivariate Cox regression analyses were performed on DEGs to identify the optimal prognosis-related genes. qRT-PCR was performed to verify the result. Results. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The VCAM1 pathway members CLDN5, CLDDN23, and PLCG2 work with VCAM1 to signal immune cell transmigration ( 48, 49 ). Consistent with our deconvolution results, CD163 indicates the presence of anti-inflammatory macrophages that have been polarized by IL10 and IL10RA ( 50, 51 ) and TREM2 suggests that microglia are also present ( 52 ). Together, these macrophages and microglia constitute glioma-associated macrophages/microglia (GAMs).…”
Section: Resultssupporting
confidence: 88%
“…The VCAM1 pathway members CLDN5, CLDDN23, and PLCG2 work with VCAM1 to signal immune cell transmigration ( 48, 49 ). Consistent with our deconvolution results, CD163 indicates the presence of anti-inflammatory macrophages that have been polarized by IL10 and IL10RA ( 50, 51 ) and TREM2 suggests that microglia are also present ( 52 ). Together, these macrophages and microglia constitute glioma-associated macrophages/microglia (GAMs).…”
Section: Resultssupporting
confidence: 88%
“…The expression of macrophage-related immune checkpoints among trajectories was consistent with the immune/stromal scores and the distribution of macrophages among molecular subtypes. These particular immune checkpoints included the iconic M2 receptors CD206 and CD163 [50][51][52][53] ; CD47-SIRPα, which were functioning as ligand-receptor pairs that transmit phagocytosis signals of macrophages 54,55 ; LILBRs family members of LILRB1, ILLRB2, and LILRB4, who directly expressed on the surface of tumor cells and stimulated tumor cells growth by combining with MHC-56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, LRRK2 correlates with macrophage infiltration in GBM [ 37 ]. Meanwhile, CD163 was also associated with immune infiltration in glioblastoma multiforme [ 38 ]. Moreover, a recent study showed TUBA1C expression was positively related to infiltration levels of multiple immune cells, such as CD8 T+ cells and neutrophils [ 39 ].…”
Section: Discussionmentioning
confidence: 99%